Evaluating insulin information provided on discharge summaries in a secondary care hospital in the United Kingdom - Amie Bain; Lois Nettleship; Sallianne Kavanagh; Zaheer- (Taylor & Francis Group, 2017)
Background Prescribing errors at the time of hospital discharge are common and could potentially lead to avoidable patient harm, especially when they involve insulin, a high-risk medicine widely used for the treatment of diabetes mellitus. When information regarding insulin therapy is not sufficiently communicated to a patient's primary care provider, continuity of care for patients with diabetes may be compromised. The objectives of this study were to investigate the nature and prevalence of insulin-related medication discrepancies contained in hospital discharge summaries for patients with diabetes. A further objective was to examine the timeliness and completeness of relevant information regarding insulin therapy provided on discharge summaries. Methods The study was undertaken at a large foundation trust hospital in the North of England, UK. A retrospective analysis of discharge summaries of all patients who were being treated with insulin and were included in the 2016 National Inpatient Diabetes Audit was conducted. Insulin regimen information provided on discharge summaries was scrutinised in light of available medical records pertaining to the admission and current national recommendations. Results Thirty-three (79%) out of the 42 patients included in the study had changes made to their insulin regimen during hospital admission. Eighteen (43%) patients were identified as having an error or discrepancy relating to insulin on their discharge summary. A total of 27 insulin errors or discrepancies were identified on discharge, most commonly involving non-communication of an insulin dose change (n = 8) and wrong insulin device (n = 7). Seventeen issues relating to completeness of insulin information were identified, including the omission of the prescribed time of insulin administration (n = 10) and unexplained insulin dose change (n = 4). Two patients who had insulin-related errors identified on their discharge summaries were readmitted to hospital within 30 days of discharge due to poor diabetic control. Conclusions This small-scale study demonstrates that errors and discrepancies regarding insulin therapy on discharge persist despite current insulin safety initiatives. Poorly communicated information regarding insulin therapy may jeopardise optimal glycaemic control and continuity of patient care. Insulin-related information should be comprehensively documented at the point of discharge. This is to improve communication across the interface and to minimise risks to patient safety.